Invasive splenic mucormycosis due to Rhizopus microsporus during chemotherapy for acute monocytic leukemia: a case report and literature review - Peng, Xiru; Wei, Zixiu; Wang, Lijuan; Cheng, Juan (Frontiers in Oncology, 2023)
Mucormycosis is a rare opportunistic fungal infection associated with high mortality that typically occurs in immunocompromised patients. It is difficult to diagnose owing to non-specific clinical manifestations, the serologic index, imaging features, and the limitations of diagnostic methods. The incidence of invasive splenic mucormycosis is extremely rare, with only a few cases documented in the literature. We report a survival case of invasive splenic mucormycosis involving the liver caused by Rhizopus microsporus in a patient during consolidation therapy for acute monocytic leukemia (AML-M5). The patient initially presented with recurrent fever and splenomegaly accompanied by multiple focal hypodensities unresponsive to empiric anti-infective treatment. Splenic mucormycosis was diagnosed by Contrast-Enhanced Ultrasonography (CEUS) and metagenomic next-generation sequencing (mNGS). However, surgical intervention carries a high risk due to the progressive involvement of the liver in invasive splenic mucormycosis. Fortunately, monotherapy with amphotericin B was effective, and the patient underwent allo-HSCT. This case aims to emphasize the importance of utilizing mNGS and CEUS for the timely diagnosis of mucormycosis to help clinicians identify splenic mucormycosis and initiate appropriate therapy as soon as possible to improve therapeutic efficacy and prognosis.